Evaluation of the Effect of Flexi-Bar In Patients With Low Back Pain: Narrative Review Article - Fatemeh Amiri; Mohammad Mohsen Roostayi (Ṭibb-i Tavānbakhshī, 2022)
Background and Aims: Low back pain is one of the most common and costly musculoskeletal problems that affects more than 80% of people in the community at some point in their lives. Control of pain and functional disability of patients with low back pain is the most important part of physiotherapy and rehabilitation, and recently, the use of vibrating tools to achieve this goal has been considered. A flexi-bar is a vibrating instrument that causes low-frequency vibration in the body through active movements in the upper extremities. According to the articles, these vibrational stimulations, in addition to the stimulation of vibratory receptors and pain relief, can activate muscle spindles, increase the activity of alpha neurons, and improve neuromuscular control in the trunk muscles. The aim of this review study was to evaluate the effectiveness of flexi-bar as a vibrational exercise therapy tool in the rehabilitation of patients with low back pain.Methods: In this study, an electronic search was performed in PubMed, Scopus, and Google Scholar search engines from 2000 to 2020, and studies that examined the effectiveness of flexi-bar on pain, functional disability, or trunk muscle activity in patients with low back pain or healthy individuals were selected. The keywords of low back pain, flexi-bar, body blade, vibrating rod, and trunk muscle activity were used for the search.Results: Using keywords and considering the inclusion and exclusion criteria, 17 articles that were most relevant to the subject of this article were reviewed.Conclusion: The results of these studies showed that flexi-bar is useful in reducing pain and improving functional disability in patients with low back pain, but more studies are needed in the future to more accurately evaluate the effectiveness of flexi-bar in trunk muscle activity in patients with low back pain.